Pursuing Strategy
XIII, 205 p.
Keywords: Formulating a strategy involves complex interactions between politicians, strategic commanders and generals in the field. The authors explore the strategic decisions made during NATO missions in Bosnia-Herzegovina, Kosovo, Macedonia, Afghanistan, Somalia and Libya.